解方程:
(1) $x^2-6 x-3=0$;
(2) $2 x^2+5 x+1=0$.
【答案】
解: (1) 配方, 得 $x^2-6 x+3^2-3^2-3=0$.
$$
(x-3)^2-12=0 \text {. }
$$
移项, 得 $(x-3)^2=12$.
两边开平方, 得 $x-3=\pm 2 \sqrt{3}$.
即 $x-3=2 \sqrt{3}$, 或 $x-3=-2 \sqrt{3}$.
所以 $x_1=3+2 \sqrt{3}, x_2=3-2 \sqrt{3}$.


(2) 这里 $a=2, b=5, c=1$.
$$
\begin{aligned}
& \because b^2-4 a c=5^2-4 \times 2 \times 1=17 > 0, \\
& \therefore x=\frac{-5 \pm \sqrt{17}}{2 \times 2}=\frac{-5 \pm \sqrt{17}}{4} .
\end{aligned}
$$
即 $x_1=\frac{-5+\sqrt{17}}{4}, x_2=\frac{-5-\sqrt{17}}{4}$.


系统推荐